Probiotics Supplementation Alleviates Endotoxemia-induced Behavioral Deficits in Mice - Babu, Gyan (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: The gut microbiota plays a critical role in maintaining normal mental health. Studies have highlighted the role of probiotics in monitoring the bacterial population and modulating the gut-brain axis. Probiotic supplementation has received considerable attention as a potential therapeutic regime for the treatment of behavioral abnormalities. The present study elucidated the modulatory role of probiotics alone or as adjuncts with an agonist of the antipsychotic peptide neurotensin (NTS1) on behavioral deficits induced by endotoxin, bacterial lipopolysaccharide (LPS). Materials and Methods: Five groups of mice were maintained: control, LPS, LPS + probiotics (Pro), LPS + NTS agonist (PD), and LPS + pro + PD. Mice were challenged with LPS (1 mg/kg bw) for 5 days, followed by supplementation of probiotics (0.6 g/kg bw), PD (50 μg/kg bw), and a combination of pro and PD for 4 weeks. Results: LPS-exposed mice showed sickness behavior (decrease in food and water intake), anxiety behavior (reduction in time duration, entries in the central square in the open-filed arena, and entries in the open arm in the elevated plus maze), and depressive behavior (increment in immobility time in the force swimming test). A significant reduction in sickness, anxiety, and depressive behaviors as compared to their LPS counterparts on supplementation of probiotics alone or in combination withNTS1 agonist; the efficacy was enhanced in the latter. Probiotics supplementation alone or in combination with NTS1 agonist, reduced the plasma levels of tumor necrosis factor-α, interleukin-6 (IL-6), and corticosterone, and increased plasma levels of IL-10 might be due to increased beneficial bacteria Bifidobacteria and a decreased population of harmful bacteria Clostridia. Conclusion: Probiotic supplementation has the potential to prevent behavioral abnormalities, restore the homeostasis of the microbiota, and may be used as a therapeutics adjunct along with other anti-psychotic drugs for mental illness.